The Effect of Using Several Types of Mulch to Control Weeds on The Growth and Yield of Mung Bean Plants - Ramadhan, Ryvandi; Saleh, Ismail (Jurnal Agrosci, 2025)
Background. The use of mulch is one method of weed control and can increase mung bean yields. Aims. This study aims to investigate the impact of various types of mulch on weed growth in mung bean plants. Methods. This research was conducted in Kepongpongan village, Talun District, Cirebon Regency. The research was carried out from October to December 2024. The experimental design employed was a randomized block design (RBD) with four treatments and six replicates. The treatment factors studied consisted of M1 (no mulch), M2 (rice straw mulch), M3 (reed mulch), and M4 (black and silver plastic mulch). Result. The results showed that this type of mulch against weeds can reduce the number of weed individuals. The use of mulch affects the weight of weeds, plant height, number of leaves, leaf area, flower age, pod weight, number of pods, seed weight, and weight of 100 seeds. Conclusion. The use of plastic mulch in this study gave the best results